Prospective Associations Between Intervention Components and Website Engagement in a Publicly Available Physical Activity Website: The Case of 10,000 Steps Australia - Davies, Cally; Corry, Kelly; Van Itallie, Anetta; Vandelanotte, Corneel; Caperchione, Cristina; Mummery, W Kerry (JMIR Publications, 2012)
BackgroundEffectiveness of and engagement with website-delivered physical activity interventions is moderate at best. Increased exposure to Internet interventions is reported to increase their effectiveness; however, there is a lack of knowledge about which specific intervention elements are able to maintain website engagement. ObjectiveTo prospectively study the associations of website engagement and exposure to intervention components for a publicly available physical activity website (10,000 Steps Australia). MethodsBetween June and July 2006 a total of 348 members of 10,000 Steps completed a Web-based survey to collect demographic characteristics. Website engagement was subsequently assessed over a 2-year period and included engagement data on website components; individual challenges, team challenges, and virtual walking buddies; and indicators of website engagement (average steps logged, days logging steps, and active users). ResultsOn average participants logged steps on 169 (SD 228.25) days. Over a 2-year period this equated to an average of 1.6 logons per week. Binary logistic regression showed that individuals who participated in individual challenges were more likely to achieve an average of 10,000 steps per day (odds ratio [OR] = 2.80, 95% confidence interval [CI] 1.45-5.40), log steps on a higher than average number of days (OR = 6.81, 95% CI 2.87-13.31), and remain an active user (OR = 4.36, 95% CI 2.17-8.71). Additionally, those using virtual walking buddies (OR = 5.83, 95% CI 1.27-26.80) and of older age logged steps on a higher than average number of days. No significant associations were found for team challenges. ConclusionsOverall engagement with the 10,000 Steps website was high, and the results demonstrate the relative effectiveness of interactive components to enhance website engagement. However, only exposure to the interactive individual challenge feature was positively associated with all website engagement indicators. More research is needed to examine the influence of intervention components on website engagement, as well as the relationship between website engagement and physical activity change.